DEBT IN THE PERSPECTIVE OF ISLAMIC LAW - Yunus, Djubaedi; Muslimin, JM (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2020)
The goal of this paper is to analyze the debt from view of Islamic law. Debt is one of the muamalah instruments in IslamÂ  that used for activities in household, companies, and countries to fulfill their life sustainability. At least in two things. First in the fulfillment of the fifth pillar of Islamic obligations, pilgrimage, but there is a polemic using debts because of the additional administrative costs (ujrah). The other side of the polemic of debt in the economic system of Islam even could prevent the world economic crisis, the global economic crisis due to debt plus interest in exchange in the capitalist economic system, but not use Islamic economic system in the world. The method used is a normative method and the analysis shows debt could be for bailout funds for pilgrimmage program as long as the debtor pay this loan as soon as possible, debt is the last option and the value of debt should be measured in accordance with the ability to avoid further misery and debt can provide economic value as long as it is used for business or trade to achieve the world welfare, and the hereafter without performing maisir, farad, usury and tyranny. Sodaqoh and giving sincerely is better than giving debt.